2020
DOI: 10.1038/s41419-020-02775-5
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic RTP801 contributes to motor-learning dysfunction in Huntington’s disease

Abstract: RTP801/REDD1 is a stress-responsive protein that mediates mutant huntingtin (mhtt) toxicity in cellular models and is up regulated in Huntington’s disease (HD) patients’ putamen. Here, we investigated whether RTP801 is involved in motor impairment in HD by affecting striatal synaptic plasticity. To explore this hypothesis, ectopic mhtt was over expressed in cultured rat primary neurons. Moreover, the protein levels of RTP801 were assessed in homogenates and crude synaptic fractions from human postmortem HD bra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 79 publications
(116 reference statements)
11
29
0
Order By: Relevance
“…Hence, we first isolated cortical and striatal crude synaptosomes from adult postmortem human brain, adult rat and mouse brains and from cultured rat cortical neurons. In all samples we observed the presence of RTP801 or its enrichment in crude isolated synaptic terminals in comparison to the initial homogenates ( Fig 1 A ), corroborating our own previous results (Martín-Flores et al , 2020). Interestingly, in cultured cortical neurons, we observed that RTP801 was expressed in the soma, dendrites and dendritic spines ( Fig 1 B ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Hence, we first isolated cortical and striatal crude synaptosomes from adult postmortem human brain, adult rat and mouse brains and from cultured rat cortical neurons. In all samples we observed the presence of RTP801 or its enrichment in crude isolated synaptic terminals in comparison to the initial homogenates ( Fig 1 A ), corroborating our own previous results (Martín-Flores et al , 2020). Interestingly, in cultured cortical neurons, we observed that RTP801 was expressed in the soma, dendrites and dendritic spines ( Fig 1 B ).…”
Section: Resultssupporting
confidence: 92%
“…Hence, we initially confirmed that RTP801 was present in the synapses from a wide range of human and murine samples, as we previously described in HD murine models and HD human postmortem samples (Martín-Flores et al , 2020). Interestingly, RTP801 was highly enriched in human and rat crude synaptosomes but not that elevated in synaptic WT mice samples.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations